The experience of living with human immunodeficiency virus among adolescents at Felege Hiwot Comprehensive Specialized Hospital Bahir-Dar, Northwest Ethiopia, A phenomenological study. - Bazezew Asfaw Guadie; Minyichil Birhanu Belete; Meseret Mekuriaw Beyene; Ayalew Kassie Melese; Tarik Yenew Tessema; Yinager Workineh (PLoS ONE)
Background Adolescents who have the human immunodeficiency virus face difficulties in their lives not just from the physical consequences of the illness but also from social stigma and discrimination. The quantitative side of this issue was the focus of earlier Ethiopian research. However, there hasn't been any prior research done extensively in Ethiopia on the real-life experiences of teenagers infected with HIV. Therefore, in order to address the real issues that these teenagers encounter, it is imperative that we investigate their lived experiences as HIV-positive adolescents. Objective The goal is to investigate the experiences that adolescents at Felege Hiwot Comprehensive Specialized Hospital who are infected with HIV have on a daily basis. Method A phenomenological approach was conducted among thirteen purposively selected adolescents at Felege Hiwot Comprehensive Specialized Hospital, Bahir-Dar, northwest Ethiopia, from March 25 to April 30, 2023. Information saturation was used to estimate the sample size. Data was gathered through semi-structured open-ended interview guides and in-depth interview techniques. The talk was recorded using an audio recorder. The data was transcribed verbatim. The conceptual translation approach was used to translate the transcribed data from Amharic to English. For additional analysis, the translated data was entered into the Atlas.ti.8 program. To demonstrate findings, the inductive thematic analysis technique was applied using illustrative quotes. Colleague feedback, member checks, and a debriefing were used to guarantee the quality of the data. Result Eleven subthemes, including main theme of "lived with burdens of immunodeficiency virus," "disclosure," "ART adherence," and "future aspiration," were used to describe the findings. The participants discussed how difficult it has been for them to deal with social, emotional, and psychological difficulties in addition to living with the HIV infection. They kept their illness a secret from others out of fear of prejudice and stigma. In conclusion, adolescents infected with the human immunodeficiency virus faced a variety of difficulties related to their mental health, relationships, emotions, and compliance. It is advised that the community get ongoing, comprehensive health education in order to prevent stigmatization and discrimination against young people who have the virus.